2022
DOI: 10.1002/term.3350
|View full text |Cite
|
Sign up to set email alerts
|

Zwitterionic keratin coating on silk‐Laponite fibrous membranes for guided bone regeneration

Abstract: Implant-related infection is one of the main challenges in periodontal diseases.According to the zwitterionic properties of keratin, we aim to develop guided bone regeneration (GBR) membrane with antibacterial and bioactivity properties using a keratin coating. In this study, electrospun silk fibroin (SF)-Laponite (LAP) fibrous membranes were developed as GBR membranes, and keratin extracted from sheep wool was electrosprayed on them. Here, the role of electrospraying time (2, 3, and 4h) on the properties of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Keratin is a well-known and accepted biomaterial with biocompatibility and physiochemical properties for tissue engineering [ 42 ]. Even though dental applications of keratin are still underexplored, recent studies have proved that keratin-modified membranes have shown promising results in pulp-dentin and periodontal tissue regeneration [ 43 , 44 ]. Thus, based on the key bioactive proteins identified by the proteomic profiling and their regenerative functions, the PDLSC-CM can be provided and further developed for therapeutical alternative in periodontal diseases and periodontium defects.…”
Section: Discussionmentioning
confidence: 99%
“…Keratin is a well-known and accepted biomaterial with biocompatibility and physiochemical properties for tissue engineering [ 42 ]. Even though dental applications of keratin are still underexplored, recent studies have proved that keratin-modified membranes have shown promising results in pulp-dentin and periodontal tissue regeneration [ 43 , 44 ]. Thus, based on the key bioactive proteins identified by the proteomic profiling and their regenerative functions, the PDLSC-CM can be provided and further developed for therapeutical alternative in periodontal diseases and periodontium defects.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, researchers are studying the hydrophilicity of materials [ 117 , 118 , 119 ]. A firm hydration layer can form a physical barrier to prevent bacteria from approaching it.…”
Section: Anti-adhesion Strategies For Titanium Implantsmentioning
confidence: 99%